ANALYSIS OF THE COMPONENT ORGANIZATION OF THE SYSTEM OF INTERNAL CONTROL OF CALCULATIONS FOR COMMODITY TRANSACTIONS AT THE ENTERPRISE - BOHATCHYK, Lyudmyla; LOPATOVSKY, Viktor; SEREVETNIK, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
It has been established that internal control, as an integral component of the successful operation of the accounting system of a business entity, is an important tool of internal control, the implementation and effective functioning of which is able not only to timely detect violations in the field of organization of accounting at the enterprise, but also to prevent improper display of information and its further accumulation in reporting. The choice of optimal components of the internal control system plays an important role in determining the strategic priorities of the enterprise, and is reflected in the improvement of its reporting indicators. It is proposed to carry out the system of internal control of settlements for commodity transactions by studying the features of the construction of internal control of settlements with suppliers, debtors, as well as the calculation and payment of VAT. For each of the directions, the purpose of the inspection was defined, a list of control procedures was formed, the components of information support were established, and methodological tools were selected. In general, the conducted studies have shown that the construction of an effective SMC of settlements for commodity transactions requires taking into account not only the peculiarities of the business entity’s activity, but also the assessment of the forms of interaction with other systems that collectively form the general system of enterprise management. The effectiveness of SVC calculations is ensured thanks to the selection of a specific set of methodological techniques for each of the verification stages.